Development of a novel high-energy electron shielding Ta/Al composite coating for electronic packaging material via cold spray. (June 2023) - Liu, Hanhui; Zhao, Heran; Ren, Yupeng; Zhang, Yubao; Cui, Xinyu; Wang, Jiqiang; Xiong, Tianying
Abstract: To protect electronic components of satellite/spacecraft from high-energy electron radiations in the geostationary earth orbit (GEO) environment, a novel radiation shielding Ta/Al composite coating was successfully deposited on electronic packaging material (Al2 O3 ) by cold spray. Results showed that the radiation shielding effectiveness (against 1 MeV electron irradiation with the delivered dose of ∼60 kGy) of the prepared coating with a thickness of 0.3 mm can reach as high as 98.5% due to the synergistic effect of Ta (high atomic number, high-Z) and Al (low atomic number, low-Z) materials. Moreover, the microstructure of the prepared coating remained intact after 1 MeV electron irradiation. Overall, cold sprayed Ta/Al composite coating exhibited excellent shielding ability against high-energy electron radiation. Highlights: A novel electron shielding Ta/Al coating was prepared by cold spray. The coating prepared on electronic packaging material was uniform, dense and well-adhered. A 0.3 mm thick Ta/Al coating can shield 98.5% of the 1 MeV electron irradiation. The Ta/Al coating retained its original microstructure after electron irradiation.